NMR-Driven Identification of Cinnamon Bud and Bark Components With Anti-Aβ Activity - Ciaramelli, Carlotta; Palmioli, Alessandro; Angotti, Irene; Colombo, Laura; De Luigi, Ada; Sala, Gessica; Salmona, Mario; Airoldi, Cristina (Frontiers in Chemistry, 2022)
The anti-Alzheimer disease (AD) activity reported for an aqueous cinnamon bark extract prompted us to investigate and compare the anti-amyloidogenic properties of cinnamon extracts obtained from both bark and bud, the latter being a very little explored matrix. To this aim, we prepared the extracts with extraction different procedures (alcoholic, hydroalcoholic or aqueous). An efficient protocol for the rapid analysis of NMR spectra of cinnamon bud and bark extracts was setup, enabling the automatic identification and quantification of metabolites. Moreover, we exploited preparative reversed-phase (RP) chromatography to prepare fractions enriched in polyphenols, further characterized by UPLC-HR-MS. Then, we combined NMR-based molecular recognition studies, atomic force microscopy, in vitro biochemical and cell assays to investigate the anti-amyloidogenic activity of our extracts. Both bud and bark extracts showed a potent anti-amyloidogenic activity, being flavanols, in particular procyanidins, and cinnamaldehydes the chemical components of cinnamon hindering Aβ peptide on-pathway aggregation and toxicity in a human neuroblastoma SH-SY5Y cell line. These data, together with the previously reported ability of hindering tau aggregation and filament formation, clearly indicate cinnamon polyphenols as natural products possessing multi-target anti-AD activity. Since cinnamon is a spice increasingly present in the human diet, our results support its use for the preparation of nutraceuticals useful in the prevention of AD through an active contrast to the biochemical processes that are the basis of the onset of this disease. Moreover, the structures of cinnamon components responsible for cinnamon anti-AD activities represent molecular templates for the design and synthesis of new anti-amyloidogenic drugs.